Do myometrial lesions affect the discrepancy of pathological findings in women with endometrial hyperplasia? - Taşgöz, Fatma Nurgül; Kender, Nergis (Journal of Surgery and Medicine, 2022)
Background/Aim: Benign myometrial lesions are frequently found in pathologic specimens of hysterectomies. High rates of coexistence of these lesions with endometrial cancer have also been reported. Our aim was to evaluate the effect of myometrial lesions on the consistency of diagnoses between endometrial sampling results and final hysterectomy findings in patients with endometrial hyperplasia (EH) before hysterectomy. Methods: Two hundred seventeen patients who were diagnosed as having EH via endometrial sampling and underwent hysterectomy within three months were included in this retrospective cohort study. The patients’ preoperative and postoperative pathologic findings were compared, and discordant results were defined to be either overdiagnosed or underdiagnosed. Results: The overall diagnostic concordance between the endometrial sampling results and the final hysterectomy pathologic findings was 32.2%. The rate of concurrent endometrial carcinoma (EC) among all EH was 22.1%. The discordance between preoperative endometrial sampling and final hysterectomy specimen results was evaluated, and patients with underdiagnosis were older (60.5 years, P < 0.001), had a higher BMI (30.84 kg/m2, P < 0.001), were mostly postmenopausal (P < 0.001), had lower parity numbers (median = 2, P = 0.002), and had a lower rate of co-existing adenomyosis (P = 0.009). The rates of co-existing leiomyoma between the groups were not different. No effect of other demographic characteristics was observed in the multivariate regression analysis; however, the presence of adenomyosis was a significant independent risk factor affecting a 5.8-fold increase in overdiagnosis (-1.50; OR: 0.17 (0.05-0.50) P = 0.002) and 4.5-fold increase in underdiagnosis (-1.50; P = 0.005). Conclusion: Co-existing adenomyosis could lead to discordance of the pathologic findings in women with EH diagnoses before hysterectomy.